The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/oa.723
|View full text |Cite
|
Sign up to set email alerts
|

A foot deformity from a Romano‐British cemetery at Gloucester, England, and the current evidence for talipes in palaeopathology

Abstract: A male skeleton from the Romano-British site at Kingsholm, Gloucester, is described with abnormalities in the humerus, femur, tibia, fibula and foot. Computed tomography of the femora to enable cross-sectional analysis suggested altered normal gait to compensate for the deformity. Differential diagnoses are considered and a diagnosis of clubfoot deformity is suggested. Palaeopathological evidence for clubfoot is rare in the literature but the cases reported to date are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Roberts et al (2004) used CT scans to calculate cross‐sectional areas and second moments of area in the femora of a Romano‐British individual with a type of clubfoot deformity (also re‐investigated and re‐interpreted by Castells‐Navaro et al (2017), referencing, but without the direct inclusion of shape metrics). Regardless of the specific pathological diagnosis, what is interesting in this case are the functional interpretations drawn by Roberts et al (2004) based on the geometric properties of the femora and their asymmetries, and various morphological observations made of the joints and other long bones (e.g., bowing); namely, they suggested that it was most likely that “…the clubfoot initiated the changes in the rest of the left side bones of this individual due to changes in force transmission through the limbs” (Roberts et al, 2004, p. 401). While the majority of their argument is focused on the skeletal description and the reconstruction of the individual's activity, this conclusion provided insight into the order of events affecting the individual.…”
Section: Shape In Palaeopathological History: a Meta‐analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Roberts et al (2004) used CT scans to calculate cross‐sectional areas and second moments of area in the femora of a Romano‐British individual with a type of clubfoot deformity (also re‐investigated and re‐interpreted by Castells‐Navaro et al (2017), referencing, but without the direct inclusion of shape metrics). Regardless of the specific pathological diagnosis, what is interesting in this case are the functional interpretations drawn by Roberts et al (2004) based on the geometric properties of the femora and their asymmetries, and various morphological observations made of the joints and other long bones (e.g., bowing); namely, they suggested that it was most likely that “…the clubfoot initiated the changes in the rest of the left side bones of this individual due to changes in force transmission through the limbs” (Roberts et al, 2004, p. 401). While the majority of their argument is focused on the skeletal description and the reconstruction of the individual's activity, this conclusion provided insight into the order of events affecting the individual.…”
Section: Shape In Palaeopathological History: a Meta‐analysismentioning
confidence: 99%
“…On top of illustrating the growth of interest in shape analyses in palaeopathology, our meta‐analysis also revealed key trends that summarize how shape analyses have so far been used in palaeopathology. Overall, we identified four such themes: Describe pathological conditions and support/refute diagnoses (e.g., Berezina & Buzhilova, 2021; Berner et al, 2021; Colombo et al, 2018; Darton et al, 2015; DeSilva & Papakyrikos, 2011; Gunz et al, 2004; Hershkovitz et al, 1997; Milella et al, 2015; Rmoutilová et al, 2020; Slon et al, 2013; Thompson, 2014; Trinkaus, 2018; Vairamuthu & Pfeiffer, 2018; Viciano et al, 2017; Zhao et al, 2020) Understand how specific traits and shape characteristics predispose individuals to pathological conditions (e.g., Bédécarrats et al, 2021; Calce et al, 2018; Mansukoski & Sparacello, 2018; Mays, 2006; Plomp et al, 2012; Plomp et al, 2019; Plomp et al, 2020; Plomp, Viðarsdóttir, Weston, et al, 2015; Shepstone, 2001; Shepstone et al, 1999; Ward et al, 2010; Weiss, 2005) Identify and interpret adaptations and alterations in functional anatomy in response to pathological conditions (e.g., Berner et al, 2021; Churchill & Formicola, 1997; Gilmour et al, 2019; Lazenby & Pfeiffer, 1993; Licata et al, 2019; Micarelli et al, 2018; Roberts et al, 2004; Sparacello et al, 2016; Thompson, 2014; Trinkaus, 2018; Viciano et al, 2017; Viva et al, 2021; Zhao et al, 2020) Provide insight into aspects of physical and social experience, care practices, therapeutic interventions, and social organization (e.g., Bédécarrats et al, 2021; Chevalier, 2019; Cowgill et al, 2015; Formicola & Buzhilova, 2004; Gilmour et al, …”
Section: Sculpting a Palaeopathology Of Shapementioning
confidence: 99%
See 2 more Smart Citations
“…Documenting rarely described osteopathologies observed in single cases can provide helpful information for population-based studies (Roberts et al, 2004). This paper presents the various pathological alterations found in a single juvenile skeleton from Gnadendorf, Lower Austria.…”
Section: Introductionmentioning
confidence: 99%